Applying social networks to engineering education - DOĞAN, BUKET; ÜLKÜ, EYÜP EMRE; DEMİR, ÖNDER (WILEY, 2018)
Social networking sites (SNSs) are a popular Internet-based means for users to communicate and interact with each other. Although they have caught the attention of many researchers and are already being used as educational tools, very few studies have investigated the effects of using an SNS in engineering education. This study, therefore, aims to analyze the effects of using the Edmodo platform as a teaching and learning support tool on students' academic and practical performance in the Introduction to Information Technology and Algorithms course, as well as in the Computer Programming course they took in the following semester. It also considers the students' opinions about the Edmodo system. For this study, a total of 62 students studying in the Electrical and Electronics Engineering Department during the 2016-2017 fall semester were divided into two equally sized groups. The control group underwent a traditional face-to-face education, whereas the experimental group augmented this using the Edmodo system. A mixed-methods approach with a post-test-only control group design was used: quantitative data were obtained from student tests, together with qualitative data from follow-up interviews. The students' grades were analyzed using Student's t-test and correlation analysis, showing that the experimental group performed better in their academic and laboratory assessments and that there was a moderately positive relationship between the post-test results and performance in the subsequent Computer Programming course.
Keywords: Edmodo; engineering education; social networks; STUDENTS; FACEBOOK; EDMODO; EXPERIENCE; SITES; MEDIA